Are fishers profit maximizers? The case of Gillnetters in negros occidental and Iloilo, Philippines - Subade, Rodelio Fernandez; Raja Abdullah, Nik Mustapha (Asian Fisheries Society, 1993)
The translog profit function model was used to determine whether sampled Philippine gillnet boats or fishers were able to maximize profits from their fishing trips. The empirical results showed that the translog functional form was more appropriate than the Cobb-Douglas form. The sampled gillnet boats were not able to maximize profits. The nonprofit-maximizing behavior was found in each of the different gillnet types: drift gillnet, encircling gillnet and bottomset gillnet. The evident overfished condition of the fishery and the fishers’ satisfaction from their work were cited as the major reasons why they opted to remain in the fishery despite its nonprofitability.